Deforested habitats lack seeds of late‐successional and large‐seeded plant species in tropical montane forests. Issue 4 (22nd June 2015) - Saavedra, Francisco; Hensen, Isabell; Schleuning, Matthias; Wesche, Karsten
Abstract Questions (1) How do seed density and species richness of late‐successional, pioneer and non‐forest species change from forest interior to deforested habitats? (2) Are seed density and species richness of seed species dispersed into deforested areas enhanced by perch structures? (3) Do morphological seed traits of forest and non‐forest plant species change from the forest interior to deforested areas? Location Deforested tropical mountains of Chulumani, La Paz, Bolivia. Methods At eight study sites, we installed a system of 38 seed traps along a transect of 240 m from the forest interior (160 m from the forest margin) toward deforested areas (80 m from the forest margin). Half of the seed traps installed in the deforested areas were positioned under perch structures. We identified captured seeds to morpho‐species or species level and recorded morphological seed traits (i.e. seed mass, seed length, seed width) and species origin (i.e. late‐successional, pioneer, non‐forest species). Results Seed density and species richness of late‐successional and pioneer species declined from the forest interior toward deforested areas. Seed limitation was particularly strong for large‐seeded species. Perches in deforested areas strongly increased the density and to some extent as well as the species richness of seeds dispersed into these areas, but did not alter the composition of seed traits and species origin in comparison to seed traps without perches. Conclusions We found a strong seed dispersal limitation in deforested areas, which was mitigated by the presence of perch structures, at least in terms of seed density and species richness. However, the dispersal limitation of late‐successional plant species with large seeds was not compensated by the presence of perching structures. Nevertheless, the establishment of artificial perch structures is likely to be a promising strategy for capturing seeds in deforested areas that may establish under bracken fronds in the long term.